Implementasi Kebijakan Retribusi Parkir Tepi Jalan - Safawi, Indra; ', Sujianto; Rusli, Zaili (Jurnal Kebijakan Publik, 2012)
This study aims to determine theimplementation of the policy and the factors that influence Roadside Parking Levy in Dumai City.This study classified into descriptive analysis bahasannya where development is directed to howefforts to address the factors that affect the implementation of the policy. The results indicate theimplementation of curbside parking charges policy can not be implemented in accordance withthe desired goal, which is to create order in a parking curb and generate revenue that can contributea large Revenue. It is influenced by the resource, disposition, birokrasim structure and content ofthe policy.